2001
DOI: 10.1038/83190
|View full text |Cite|
|
Sign up to set email alerts
|

B cell development and immunoglobulin gene transcription in the absence of Oct-2 and OBF-1

Abstract: Oct-2 and OBF-1 (also called OCA-B or Bob-1) are B cell-specific transcription factors that bind to the conserved octamer site of immunoglobulin promoters, yet their role in immunoglobulin transcription has remained unclear. We generated mice in which the lymphoid compartment was reconstituted with cells that lack both Oct-2 and OBF-1. Even in the absence of these two transcription factors, B cells develop normally to the membrane immunoglobulin M-positive (IgM+) stage and immunoglobulin gene transcription is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 40 publications
2
88
1
Order By: Relevance
“…Since this motif is essential for activity of Ig gene promoters, these authors suggested a causative link between absence of these two transcription factors and Ig gene expression. We have largely confirmed lack of Oct-2 and OBF-1 in cell lines and in pathological specimens of classical HL, but several lines of evidence suggest that deficiency of these two transcription factors cannot solely account for loss of Ig gene transcription in HRS cells: (1) Although octamer-dependent reporter constructs including Ig gene promoters may be reactivated in HRS cell lines when cotransfected with Oct-2 and OBF-1 expression plasmids, transcription from endogenous Ig loci is not reactivated (Hertel and Junker, unpublished); (2) Ig gene transcription does not strictly require Oct-2 and OBF-1 because B cells derived from knock-out mice engineered to lack functional Oct-2, OBF-1 or both genes produce Igs (Schubart et al, 2001); (3) the IgH locus is transcribed in cell lines lacking Oct-2 and OBF-1 (Junker, unpublished). Thus, these findings imply that the ubiquitous transcription factor Oct-1 together with one or more, as yet unidentified cofactors, plays a more central role in the control of Ig gene transcription than has previously been recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Since this motif is essential for activity of Ig gene promoters, these authors suggested a causative link between absence of these two transcription factors and Ig gene expression. We have largely confirmed lack of Oct-2 and OBF-1 in cell lines and in pathological specimens of classical HL, but several lines of evidence suggest that deficiency of these two transcription factors cannot solely account for loss of Ig gene transcription in HRS cells: (1) Although octamer-dependent reporter constructs including Ig gene promoters may be reactivated in HRS cell lines when cotransfected with Oct-2 and OBF-1 expression plasmids, transcription from endogenous Ig loci is not reactivated (Hertel and Junker, unpublished); (2) Ig gene transcription does not strictly require Oct-2 and OBF-1 because B cells derived from knock-out mice engineered to lack functional Oct-2, OBF-1 or both genes produce Igs (Schubart et al, 2001); (3) the IgH locus is transcribed in cell lines lacking Oct-2 and OBF-1 (Junker, unpublished). Thus, these findings imply that the ubiquitous transcription factor Oct-1 together with one or more, as yet unidentified cofactors, plays a more central role in the control of Ig gene transcription than has previously been recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that the coactivator Bob-1 can interact efficiently with the POU (pronounced pow) domains of Oct-1 and Oct-2 as well as the octamer element and is necessary for Ig promoter activation in B lymphocytes. 24,26,[33][34][35]37 However, we did not detect Bob-1 expression in HeLa S3 or HT-29 cells (data not shown). Our findings of the overexpression of Oct-1, but not of Oct-2, indicate that Oct-1 has a major role in promoting Ig expression in non-B cancer cells.…”
Section: Regulation Of Ig Transcription In Cancer Cellsmentioning
confidence: 66%
“…Oct-2 and Bob-1 are mature B-cell-specific transcription factors, whereas Oct-1 is expressed during the early development of B cells and other types of cell. 23,24 The aforementioned specific transcription factors regulate orderly Ig gene rearrangement and transcription in B cells through site-specific Ig gene regulators.…”
Section: Introductionmentioning
confidence: 99%
“…In B cells containing an inducible OBF-1 allele, it was found that the activity of octamer-dependent reporters depended on OBF-1 (11). Yet, in vivo data from OBF-1 ÏȘ/ÏȘ mice indicated that OBF-1 is dispensable for early antigen-independent B cell development and that the level of unswitched Ig mu gene transcription in mature B cells is unaffected in the absence of this coactivator (10,(12)(13)(14). OBF-1 appears to play a role in cell survival at early B cell stages, and, in the absence of OBF-1, a reduction of transitional B cells in the spleen was observed.…”
mentioning
confidence: 99%